Collaborative Governance In The Development of Malapari Plants as Biodiesel Feedstock (Analysis of Collaborative Governance Readiness) - Hestiana, Mia; Lutfi, Achmad (Pelopor Publikasi Akademika, 2024)
The role of coal in energy supply is in line with the increasing demand for power plant construction in several regions driven by economic growth and income. The purpose of this study is to determine collaborative governance in the development of malapari plants as biodiesel feedstock. This research uses qualitative research to understand social phenomena with a normative legal approach that prioritizes literature studies, data collection activities from various literature both from libraries and other places. The results obtained are education and training to farmers on sustainable agricultural practices and natural resource management is also a precondition that must be done. This knowledge can help farmers adopt practices that support the sustainable growth of malapari plants. Effective pest and disease management strategies are needed to protect malapari plants from attacks that can reduce crop yields. The conclusion of this study is that training and education programs need to be expanded to increase farmers' understanding of sustainable agricultural practices, processing technology, and agrofuel management. This can help improve the quality and quantity of malapari crop yields. Socialization to the community regarding the benefits of developing malapari plants as biofuels and their positive impacts on the environment needs to be strengthened. Public acceptance is considered to be able to support the growth of this industry.